Development of a Renewable Energy Based Smart Home Appliance Trainer Kit for Learning Technology Development - Saifur Risal; Muhammad Harlanu; Yeri Sutopo (Journal of Vocational and Career Education, 2026)
This research aims to develop a renewable energy based smart home appliance trainer kit utilizing a solar power generation system and to evaluate its feasibility, practicality, and effectiveness in improving student learning outcomes. The study is situated within the technology development learning element and addresses global issues in the electrical power industry in Phase E of the Merdeka Curriculum. A Research and Development approach was employed using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research participants consisted of tenth grade students of Electrical Power Engineering at SMK Nurul Barqi Semarang as the experimental group and students from SMKN 3 Semarang as the control group. Data were collected through expert validation of learning materials and media, teacher practicality questionnaires, and student learning outcome assessments. Data analysis techniques included feasibility analysis, normality testing, homogeneity testing, N Gain analysis, and independent t test. The results indicate that the trainer kit was successfully developed using a stand-based structure with a plug and play system supported by banana socket connections. Expert validation classified the learning media as very feasible, with mean scores of 4.67 from media experts and 4.88 from material experts. Practicality evaluation conducted by ten Electrical Power Engineering teachers resulted in a score of 96.43%, indicating a very practical category. Effectiveness testing showed an improvement in students cognitive learning outcomes, with an average N Gain value of 56.83%, categorized as moderately effective. Furthermore, the independent t test revealed a statistically significant difference in learning effectiveness between students who used the trainer kit and those who followed conventional learning methods.